User Acceptance Of Mobile Augmented Reality For Tourism By Adopting The UTAUT Model - Low, Wei Shang (2019)
Of recent times, Augmented Reality (AR) applications have been seen to be able to execute through numerous seamless channels through our smartphones. However, the problem statement identified in the research shows that Malaysia therefore being a country flooded with mobile devices, still have many users who are unaware of the possibilities of AR and making the technology being limited among the mobile users here. That is why the objectives of this research will be to investigate a user’s acceptance of AR technology using the Unified Theory of Acceptance and Use of Technology (UTAUT) model in Malaysia. From here, the research can identify relevant acceptance rate of AR technology, which can then be used to gather and analyse data for this research. The final objective will then be targeted to validate the analysed acceptance rate based on UTAUT. The research is targeted to develop and construct an AR application through a mobile phone which is able to merge 3D AR models of historical monuments. These historical monuments are then identified to be within UNESCO World Heritage Site of Malacca. Such mobile application will enable fellow tourists to be able to get multiple data and information via the monuments from the 3D object models which will be constructed and displayed via AR. The AR models are believed to be able to give tourists an alternative method to visit or view the actual monuments which can enable the prevention of overcrowding effect while at the mean time enforces heritage preservation. Using fellow tourists in Melaka as respondents, the researcher can determine user’s acceptance of the mobile applications in AR based on the methodologies of UTAUT. The main UTAUT methodology used here for the research contains constructs which has been finalized. These includes Performance Expectancy (PE), Effort Expectancy (EE), Facilitating Conditions (FC), and Perceived Playfulness (PP) which are then used as determinants of a user’s Behavioral Intention (BI). Through numerous testing and analysis, user’s acceptance for the AR application was tested and affirmed. Finally, it was found that the coefficient table confirms PE, FC and PP to have a positive significant effect to the model while EE was insignificant. This is due to the high ownership of smartphone device adoption of late therefore allowing users to have minimal effort to use the AR application.